Religious intermittent fasting: Effects on liver health, metabolic markers, and gut microbiota in type 2 diabetes patients - Svenja Sydor; Ender Engin; Samantha Wittek; Peter Lemmer; Jan Best; Martin Steinmetz; Anja Figge; Andreas Jähnert; Mustafa Özcürümez; Martina Broecker-Preuss; Wing-Kin Syn; Ali Canbay; et al. (Clinical Nutrition Open Science)
Summary: Background & Aims: Religious fasting during Ramadan involves a time-restricted intake of food and drink, which can be compared to intermittent fasting. In this study, we aimed to investigate the impact of a one-month fast on liver damage, glucose metabolism and changes in gut microbiota in a cohort of type 2 diabetic patients. Methods: Blood and fecal samples were taken before and after the four-week fasting period. Serum was analyzed for various parameters related to liver damage and monitor diabetes and lipid metabolism. Fecal samples were used to analyze the 16sRNA microbiota. Liver status was assessed using transient elastography measurement (TEM) and the controlled attenuation parameter (CAP). Results: Significant weight loss was observed in patients after the fasting period, and liver transaminases, triglycerides as well as the apoptosis marker M30 and serum adiponectin were significantly reduced after intermittent fasting. Analysis of microbiota showed an increase in species richness after four weeks. Conclusion: In this cohort of type 2 diabetes patients, a reduction of markers indicating liver damage (M30) was observed, though most values remained within the normal range. Health benefits of fasting were not sustained, as M30 levels increased after fasting ended suggesting that the beneficial effects may be due to intermittent fasting itself rather than reduced calorie intake. The mechanisms potentially affect hormonal, inflammatory and stress- and circadian rhythm-related pathways.